SIMULATION OF CONTROL STRATEGY FOR INTERNATIONAL MARKETING SERVICES - Korzh, Marina; Akіmova, Luidmila; Chub, Irina (Proceedings of National Aviation University (archive), 2017)
The main purpose of this article is to develop a general model of integrated management of marketing activities from an international perspective, given the relationship of its parts to each other and the external environment and the cyclical nature of the process, and the construction of a general model for evaluating the performance of international marketing system. Results: In modern conditions high-quality products are necessity-term, but not sufficient to achieve the successful operation of the market. To optimize the above goal should be to work out issues such as the definition of the requirements of potential customers, the timing, location and conditions of the transaction, that is, the seller must offer the buyer at a particular moment only the product that the best way to satisfy existing need for the latter. This may explain the reason for the proposed buyers of high-quality goods are distributed in the market of one country and cannot find it in another. Discussion: The information presented in this article marketing management model allows you to organize all marketing activities and events, and do them not by chance, but in the complex, taking into account their relationship and interaction. As well as the opportunity to working with mesh product and market development to identify new attraction activities and evaluate them in terms of compliance with the overall objectives and company resources. In addition, the proposed method of assessing the effectiveness of a marketing system is universal, and it allows you to analyze the effectiveness of the functioning of the marketing of individual enterprises, regardless of scope, given the impact of all factors.